Pengaruh Green Accounting dan Kinerja Lingkungan terhadap Nilai Perusahaan - Nikmah, Zulfatu; Utami, Endang Sri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
In recent years, the basic and chemical industries have experienced a decline in stock prices attributable to heightened investor awareness regarding environmental issues and the implementation of more stringent environmental regulations. Environmental factors such as increased pollution and carbon emissions resulting from industrial activities have emerged as significant concerns that may influence firm valuation. This study aims to investigate the effect of green accounting practices and environmental performance on the value of companies operating in the basic and chemical sectors listed on the Indonesia Stock Exchange over the period 2021–2023. Specifically, the research evaluates the influence of environmental management and environmental cost reporting on corporate valuation from an investor’s perspective, employing a descriptive quantitative methodology based on a panel data model. The sample comprises 63 companies, with secondary data sourced from financial statements and PROPER KHLK assessments. The results indicate that green accounting does not exert a statistically significant effect on firm value, whereas environmental performance has a negative impact. These findings suggest that although companies have undertaken environmental management and cost reporting initiatives, such factors have yet to become decisive considerations for investors. Enhancements in environmental performance may elevate operational costs, thereby potentially diminishing firm value.